Two-Stage Exchange Arthroplasty for Periprosthetic Shoulder Infection Is Associated with High Rate of Failure to Reimplant and Mortality - Doruk Akgün (MDPI AG, 2021)
Background: Patients with a periprosthetic joint infection (PJI) of the shoulder, who fail to undergo reimplantation in an attempted two-stage exchange seem to be neglected in the current literature. The aim of this study was to assess the clinical course of patients after the first stage in the process of an attempted two-stage exchange for shoulder PJI. Methods: After a retrospective review of our institutional database between 2008 and 2018, 49 patients, who were treated with an intended two-stage exchange for shoulder PJI, were identified. Patients’ demographics, laboratory and health status parameters, along with records of clinical outcome were collected. The primary outcome measurements analyzed were infection eradication, successful reimplantation, and patient survival. Results: Reimplantation was completed in only 35 (71%) of 49 cases and eradication of infection was achieved in 85.7% of patients with successful reimplantation after a mean follow-up duration of 5.1 years (1.1 to 10.2 years). Reasons for failure to reimplant were premature death in 36%, high general morbidity in 29%, satisfaction with the current status in 21%, or severe infection with poor bone and soft tissues in 14% of the patients. Of the 14 cases without reimplantation, eradication rate of infection was 57% after a mean follow-up of 5 years (2.6 to 11 years). The overall mortality rate of the entire cohort was 25% at the latest follow-up and 10% within ninety days after implant removal. Patients who deceased or did not undergo reimplantation during the follow-up were significantly older and had a significantly higher Charlson comorbidity index (CCI). Conclusions: While the two-stage exchange arthroplasty can lead to high rates of infection eradication, a considerable subset of patients never undergoes the second stage for a variety of reasons. Shoulder PJI and its treatment are associated with a high risk of mortality, especially in patients with older age and higher CCI.